MODERN TEACHING APPROACHES OF ENGLISH LANGUAGE IN NON-SPECIALIZED UNIVERSITIES - Maksudov Umed Olimovich (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article is devoted to the problem of studies of modern methods and techniques of teaching foreign (English) language the students of non-linguistic University. As an example, several modern and relevant methods of teaching English are given. In this article, special attention is paid to the specific application of methods in the educational process. The article also considers the effectiveness of methods of teaching a foreign language, as it contributes to the formation and development of various abilities, skills, general educational and professional competencies of important for the modern specialist. The result of the analysis of modern contradictions in the teaching of a foreign language is given in a non-linguistic environment of a modern Institute or University. At present, in the era of globalization and scientific - technological progress, the need for foreign language proficiency of future specialists is increasing. In particular, it concerns students of non-linguistic specialties, for which it is the main necessity. One of the ways to improve the efficiency of teaching a foreign language is considered to be the introduction of the methods of personality-oriented learning in the educational process.